2002
DOI: 10.1034/j.1399-3054.2002.1140204.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall modifications of bean (Phaseolus vulgaris) cell suspensions during habituation and dehabituation to dichlobenil

Abstract: Bean (Phaseolus vulgaris L.) cell suspensions were adapted for growth in 12 &mgr;M dichlobenil (2,6-dichlorobenzonitrile or DCB) by a stepwise increase in the concentration of the inhibitor in each subculture. Non-tolerant suspensions (I50 = 0.3 &mgr;M) gave rise to single cells or small clusters while tolerant cell suspensions (I50 = 30 &mgr;M) grown in DCB formed large clusters. The cells in these clusters were surrounded by a thick and irregular cell wall with a lamellate structure and lacking a differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 27 publications
(76 reference statements)
9
64
0
Order By: Relevance
“…[36][37][38][39] If quinclorac inhibited cellulose biosynthesis, it would be likely for quinclorac-habituated cells to present reduced amounts of this polymer and an increase in pectic polysaccharides, in a similar manner to that shown by isoxabenhabituated and DCB-habituated bean cells. 30,31,40 However, the spectra and multivariate analyses performed on cell walls from quinclorac-habituated cells did not detect these features. When compared with non-habituated cells, the main difference was due to a decrease in peaks related to pectins and an enhancement in those assigned to proteins.…”
Section: Using Ftir To Monitor the Effects Of Cbismentioning
confidence: 97%
See 1 more Smart Citation
“…[36][37][38][39] If quinclorac inhibited cellulose biosynthesis, it would be likely for quinclorac-habituated cells to present reduced amounts of this polymer and an increase in pectic polysaccharides, in a similar manner to that shown by isoxabenhabituated and DCB-habituated bean cells. 30,31,40 However, the spectra and multivariate analyses performed on cell walls from quinclorac-habituated cells did not detect these features. When compared with non-habituated cells, the main difference was due to a decrease in peaks related to pectins and an enhancement in those assigned to proteins.…”
Section: Using Ftir To Monitor the Effects Of Cbismentioning
confidence: 97%
“…31,32 As in DCB-habituated bean calluses, FTIR spectra from habituated suspension-cultured cells showed increased peaks corresponding to uronic acids, ester linkages and carboxylic linkages, indicating a progressive enrichment in pectins as the level of habituation to the inhibitor increased. Throughout the dehabituation process, peaks assigned to pectins gradually decreased, in such a way that FTIR spectra from longterm dehabituated cell walls resembled the spectra from nonhabituated cells.…”
Section: Using Ftir To Monitor the Effects Of Cbismentioning
confidence: 99%
“…The habituation of bean calluses to dichlobenil was associated with a high scavenging capacity of ROS, mainly by CIII-POX activity (García-Angulo et al, 2009) and also with the capacity of the cells to divide and expand with a modified cell wall in which the xyloglucan-cellulose network had been partially replaced by pectins (Encina et al, 2001(Encina et al, , 2002. However, quinclorac-habituated bean cells have a non-modified cell wall (Alonso-Simón et al, 2008) and, as was observed in this study, this habituation seemed to be related to a high antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, modifications in cell wall composition due to the habituation process were analysed (Alonso-Simón et al, 2008). The results obtained showed that the mechanism of bean cells habituation to quinclorac differed from that reported for well-known CBIs such as dichlobenil (Encina et al, 2001(Encina et al, , 2002 or isoxaben (Díaz-Cacho et al, 1999). In the dichlobenil and isoxaben-habituation processes, bean cells developed the capacity to divide and expand, with a modified cell wall in which the xyloglucan-cellulose network had been partially replaced by pectins.…”
Section: Introductionmentioning
confidence: 99%
“…This alcohol insoluble residue (AIR) was dried at 60ºC for 2 days. AIR was then de-starched, treated with acidified phenol and washed with organic solvents to obtain the cell wall residue as previously described [54,55].…”
Section: Cell Wall Analysismentioning
confidence: 99%